A self-healable polymer binder for Si anodes based on reversible Diels–Alder chemistry. (20th December 2020) - K.K., Rajeev; Nam, Jaebin; Kim, Eunsoo; Kim, Yeonho; Kim, Tae-Hyun
Abstract: Polymeric binders that interact strongly with Si can overcome a rapid capacity fading caused by its large volumetric changes (around 400%) during the charge-discharge process when Si was used as a next generation anode material in lithium ion batteries (LIBs). Among them, poly(acrylic acid) (PAA) is known to improve cell cyclability by enhancing the mechanical properties of Si through hydrogen bonding. This study added 1, 6-bismaleimide (BMI) as a crosslinker to furfurylamine-functionalized poly(acrylic acid) (FPAA) and formed a 3D crosslinked polymer network based on thermal Diels–Alder (D–A) click chemistry, which was then used as a new polymer binder for the Si anode. Having the reversible nature of D–A chemistry, the crosslinked network exhibited a self-healing property. The Si electrode with the D-A-adduct binder (DA-PAA) had excellent adhesive strength with regards to Si. After 200 cycles, it recorded a reversible capacity of 1076 mAh g −1 and a high Coulombic efficiency of 99.7%, both of which were much higher than the values obtained for typical commercial binders. Graphical abstract: Image, graphical abstract